Self-reported prevalence, type, severity and management of musculoskeletal injuries among high school rugby players in the Nelson Mandela Bay metropole - Louw, Cecilia Elizabeth (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScPhysio)--Stellenbosch University, 2019.